Determination of T Cell Responses in Thai Systemic Sclerosis Patients. (7th March 2022) - Likhit, Oranit; Louthrenoo, Worawit; Pattanakitsakul, Sa-nga; Suttitheptumrong, Aroonroong; Hannongbua, Supot; Rungrotmongkol, Thanyada; Noguchi, Hiroshi; Takeuchi, Fujio; Boonnak, Kobporn
Abstract : Objectives. This study is aimed at determining the role of T cells by assessing the numbers of IFN- γ - and IL-2-secreting T cells following stimulation with peptides derived from DNA topoisomerase-I protein in Thai SSc patients. Methods. Fifty Thai SSc patients and 50 healthy controls (HC) joined this study. IFN- γ and IL-2 levels upon stimulation of T cells with 6 peptides derived from DNA topoisomerase-I protein were determined. Anti-nuclear antibodies (ANA) and anti-Scl-70 antibodies were determined by using the ELISA method. Results. In SSc patients, we detected a significantly higher number of IFN- γ - and IL-2-secreting CD8 + T cells than IFN- γ - and IL-2-secreting CD4 + T cells after stimulation with pooled peptides derived from DNA topoisomerase-I protein. A similar percentage of CD4 + IL-2 +, CD4 + IFN- γ +, and CD8 + IL-2 + were detected following stimulation with DNA topoisomerase-I protein -in SSc patients with anti-Scl-70 antibody (SSc/anti-Scl-70 + ) and those without. In contrast, the amount of CD8 + IFN- γ + cells was significantly higher in SSc/anti-Scl-70 + than those without. Stimulation with individual peptides showed that CSLRVEHINLHPELD (sPep3; 15 amino acids; position 505-519 of DNA topoisomerase-I protein) was the optimal epitope that induced T cells secreting the highest levels of IFN- γ and IL-2. A higher percentage of IFN- γ + CD4 + T cells was detected in SSc/anti-Scl-70 + than those without the following stimulation with peptides 2 (amino acid position 475-486 [RAVALYFIDKLA] of protein DNA topoisomerase). Conclusion. The results from this study emphasize the critical role of DNA topoisomerase-I peptides on the activation of T cells in SSc patients. The findings provide a better understanding of SSc's immunopathogenesis and may lead to the development of diagnostic tools and specific treatments for SSc in the future.